Proceedings Frontiers in Education 35th Annual Conference
DOI: 10.1109/fie.2005.1611889
|View full text |Cite
|
Sign up to set email alerts
|

Using the Kolbe A™ Conative Index to Study the Retention of Computer Science Students

Abstract: Recent studies at California State University, Northridge using the Kolbe A™ index have shown differences in conative profiles between computer science students near graduation and those just entering the program. Since conation, or a person's inherent talent or natural way of doing things, relates to how a student approaches learning, it may provide clues as to why some students quit the program prior to graduation. The Kolbe instrument used in this study is a tool for measuring conative talents. It has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
4

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 10 publications
1
3
0
4
Order By: Relevance
“…Even at the freshman level a lack of conative diversity is present in engineering. This phenomenon was also shown by Lingard et al 10 . Typically successful engineering students will be insistent Fact Finder and/or insistent Follow Thru.…”
Section: Concept Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Even at the freshman level a lack of conative diversity is present in engineering. This phenomenon was also shown by Lingard et al 10 . Typically successful engineering students will be insistent Fact Finder and/or insistent Follow Thru.…”
Section: Concept Introductionsupporting
confidence: 81%
“…Further, a 2005 study provides evidence that students with certain conative strengths either preferentially self-select for engineering programs, or are more likely to persist in those programs. This suggests that students with alternative strengths may be discouraged somewhere along the way from pursuing engineering degrees 10 . Incorporation of conation into the curriculum may improve retention in STEM and persistence of diversity in conative strengths.…”
Section: Introductionmentioning
confidence: 99%
“…Las funciones objetivo del modelo están orientadas a minimizar el costo de entrenamiento, minimizar la distancia entre las capacidades del empleado y los requerimientos del trabajo y minimizar las desviaciones de la sinergia deseada. La sinergia es medida a partir de factores relacionados con el Kolbe Conative Index [54]. Factores relacionados con la experiencia, la educación, motivación, experticia y las aptitudes de los empleados, complementan la conformación de equipos.…”
Section: Página 27unclassified
“…For example, Paimin et al (2011) performed a study examining cognitive, affective and conative factors in persistence and found that learning intention (a conative measure) was crucially influential in students' levels of persistence in engineering, and affirmed the importance of identifying these intentions and fostering the link between intention and motivation for individual students (Paimin et al 2011). Further, Lingard, Berry et al (2005) provide evidence of students with certain conative strengths either preferentially self-select for engineering programs, or are more likely to persist in those programs. This suggests that students with alternative strengths may be discouraged somewhere along the way from pursuing engineering degrees (Lingard et al 2005).…”
Section: Future Workmentioning
confidence: 99%
“…Further, Lingard, Berry et al (2005) provide evidence of students with certain conative strengths either preferentially self-select for engineering programs, or are more likely to persist in those programs. This suggests that students with alternative strengths may be discouraged somewhere along the way from pursuing engineering degrees (Lingard et al 2005). …”
Section: Future Workmentioning
confidence: 99%